The new rules of retail : competing in the world's toughest marketplace - Lewis, Robin, 1940-; Dart, Michael (NY : St. Martin's Press, 2014)
"In The New Rules of Retail , industry gurus Robin Lewis and Michael Dart explained how unprecedented consumer power, enabled by technology and globalization, is revolutionizing retail. They warned that survival in these dynamic times called for a business model based on three distinct competencies: preemptive, perpetual distribution; a neurological customer connection; and total control of the value chain. In the years since that book published, many of their predictions have come true. Now, they revisit timeless case studies like Ralph Lauren and Sears, as well as new additions like Trader Joe's, Lululemon, and Warby Parker, to assess how retailers must continue to evolve in the era of e-commerce, data mining, and tiered distribution. They also identify the five current trends that are currently driving consumer demand, including technology integration and channel consolidation, as exemplified by Jeff Bezos at Amazon. This is a fully revised and updated guide from two proven retail prognosticators"--
Includes bibliographical references and index.
Keywords: Retail trade; Retail trade -- Management; Retail trade -- Technological innovations; Wholesale trade; Consumer satisfaction; BUSINESS & ECONOMICS / Commerce